2011
DOI: 10.1016/j.jana.2010.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Aging With HIV: A Cross-Sectional Study of Comorbidity Prevalence and Clinical Characteristics Across Decades of Life

Abstract: Nurses and nurse practitioners require information on the health problems faced by aging HIV-infected adults. In this descriptive, cross-sectional study, we reviewed the electronic medical records of 1,478 adult patients seen in an HIV clinic between May 2006 and August 2007 to examine patterns of comorbidities, and immunological and clinical characteristics across each decade of life. With increasing age, patients were found to have lower HIV viral loads, more prescribed medications, and a higher prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
162
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(177 citation statements)
references
References 24 publications
11
162
1
3
Order By: Relevance
“…As aging with HIV becomes commonplace, it is inevitable that psychiatrists will be facing more of such complex patients to manage especially since available studies have reported a higher prevalence rate of psychiatric and medical co-morbidities in HIV patients [30,31]. Specifically-trained HIV psychiatrists are few in number, so the onus is on the general hospital psychiatrist to combine up-to-date knowledge with clinical acumen and sound clinical practice so as to provide these complex patients with the best available care.…”
Section: Discussionmentioning
confidence: 99%
“…As aging with HIV becomes commonplace, it is inevitable that psychiatrists will be facing more of such complex patients to manage especially since available studies have reported a higher prevalence rate of psychiatric and medical co-morbidities in HIV patients [30,31]. Specifically-trained HIV psychiatrists are few in number, so the onus is on the general hospital psychiatrist to combine up-to-date knowledge with clinical acumen and sound clinical practice so as to provide these complex patients with the best available care.…”
Section: Discussionmentioning
confidence: 99%
“…8 Baik karena proses penuaan yang dipercepat ataupun faktor gaya hidup, tingkat komorbid non-HIV yang terkait dengan HIV meningkat seiring dengan bertambahnya usia, setara jika dibandingkan dengan populasi yang tidak terinfeksi HIV yang berusia 10-15 tahun lebih tua. [8][9][10][11][12] teori dapat mempercepat proses penuaan. 15,16 Selain itu, pada pasien HIV yang belum mendapat terapi ARV, serta pada pasien HIVusia lanjut dijumpai hal-hal sebagai berikut: 1) ekspresi limfosit T dan cyclin-dependent kinase inhibitor 2A (CDKN2A); 2) akumulasi sel T CD28-CD8+; 3) berkurangnya generasi sel T naif; 4) sel T repertoire yang rendah; 5) rasio CD4+/CD8+ yang rendah; 6) ekspansi efektor sel T CD28; 7) kurangnya respons terhadap vaksin; dan 8) berlangsungnya aktivasi sistem imun yang terjadi terus menerus.…”
Section: Pengaruh Hiv Terhadap Proses Penuaanunclassified
“…17 Tanpa diberikan terapi ARV, pasien usia lanjut dengan HIV lebih cepat mengalami penurunan hitung limfosit CD4+ dan lebih cepat memasuki stadium AIDS dan kematian jika dibandingkan dengan pasien usia muda. 10 Diberikannya terapi ARV dapat memperbaiki hal tersebut. Pasien HIV usia lanjut dapat memperoleh perlindungan yang serupa dengan pasien usia muda.…”
Section: Aspek Diagnosisunclassified
“…ART is considered a positive advancement since it supports and assists the immune system and reduces peripheral viral load; however, there is evidence that the ART used to treat HIV may be responsible for exacerbating common illnesses, especially heart, hepatic, and renal disease [42]. The comorbidities themselves can cause neuro-inflammation that can further worsen cognitive functioning [43].…”
Section: Confounding and Complicating Factorsmentioning
confidence: 99%